2012
DOI: 10.1111/j.1746-1561.2012.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the School Performance Variable Used in the International Health Behavior in School‐Aged Children (HBSC) Study Reflect Students' School Grades?

Abstract: The PSP item seems to be a valid and useful question that can distinguish groups of respondents that get good grades at school from those that do not. The meaning of PSP may be context-specific and may have different connotations across student populations from different countries with different school systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Therefore, generalization to other ethnicities and countries should be done with caution. Generalization of results to other countries should also be done with caution as the meaning of perceived school performance may have different connotations across student populations from different countries with different school systems . Furthermore, as this was a cross‐sectional study, this study is not able to determine causal relations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, generalization to other ethnicities and countries should be done with caution. Generalization of results to other countries should also be done with caution as the meaning of perceived school performance may have different connotations across student populations from different countries with different school systems . Furthermore, as this was a cross‐sectional study, this study is not able to determine causal relations.…”
Section: Discussionmentioning
confidence: 93%
“…Perceived school performance was measured with the question: “How do you think your teacher estimates your school performance compared with other classmates?” Answer categories were: very good, good, average, and less than average. The perceived school performance item seems to be a valid question that can distinguish groups of respondents that obtain good grades at school from those that do not …”
Section: Methodsmentioning
confidence: 99%
“…The response options were: excellent, very good, good, fair and poor, and the responses were coded from 1 for poor to 5 for excellent. A previous study suggested that perceived school performance item seems to be a valid and useful question to distinguish good grade students and others [35]. For SAP, we asked the following question, as it was used in the study by Kim et al [36]: “In the last 12 months, how do you rate your academic performance”?…”
Section: Methodsmentioning
confidence: 99%
“…Students marked how their achievements are evaluated by teacher(s) in comparison with other students in the class. The question was validated in some HBSC countries [23] by comparing it with more objective indicators of school performance. For the purpose of various analyses four categories of answers were limited to three: below average or average, good, and very good.…”
Section: Methodsmentioning
confidence: 99%